2021
DOI: 10.1088/1674-1056/ac1f09
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity at 44.4 K achieved by intercalating EMIM+ into FeSe*

Abstract: Superconductivity with transition temperature T c above 40 K was observed in protonated FeSe (H y -FeSe) previously with the ionic liquid EMIM-BF 4 used in the electrochemical process. However, the real superconducting phase is not clear until now. And detailed structural, magnetization, and electrical transport measurements are lacking. By using similar protonating technique on FeSe single crystals, we obtain superconducting samples with T c above 40 K. We show that the obtained superconducting phase is not H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…The optimized lattice parameters are a = b = 11.321 Å, c = 10.450 Å. The length of c parameter is in excellent agreement with the known experimental data [11]. EMIM cations are localized in the space between the nearest Se atoms of the FeSe layers.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The optimized lattice parameters are a = b = 11.321 Å, c = 10.450 Å. The length of c parameter is in excellent agreement with the known experimental data [11]. EMIM cations are localized in the space between the nearest Se atoms of the FeSe layers.…”
Section: Resultssupporting
confidence: 77%
“…Therefore, change of the Fermi surface topology upon EMIM intercalation may be the most important ingredient in the increase of reported in ref. [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear magnetic resonance. 1 H-NMR measurements at µ 0 H 3.5 T (magnetic field parallel to the crystallographic ab plane) were performed using a TecMag Apollo spectrometer coupled to a resonant circuit made of an in-series combination of a 470 pF capacitor and of a seven-loop solenoidal coil. The coil was deformed in order to mimic the flake-like shape of the crystals and to maximize the geometrical filling factor, in turn.…”
Section: Ionic Liquid Gating-induced Protonationmentioning
confidence: 99%
“…The recent observation of near-to-room-temperature superconductivity in hydrides under high pressure [1,2] has demonstrated that a superconducting (SC) state with remarkably high critical temperature not necessarily requires an unconventional electron-electron coupling mechanism. The key requirements here are high phonon frequencies, such as those associated to the hydrogen (H) vibration modes, a strong coupling of these modes to the electronic states at the Fermi level, and a non-conventional structural environment (in the specific case, stabilized by pressure) that favours such a coupling.…”
mentioning
confidence: 99%